UPAYA MENINGKATKAN SELF CONFIDENCE MAHASISWA DENGAN MENGGUNAKAN METODE INQUIRY PADA MATA KULIAH ALJABAR LINIER ELEMENTER UNIVERSITAS GRAHA NUSANTARA PADANGSIDIMPUAN - Adek Nilasari Harahap; Susi Sulastri Lubis (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
The type of research used is Classroom Action Research where the research is carried out by lecturers in their own class by implementing, implementing, and reflecting on collaborative and participatory actions with the aim of improving performance as a lecturer so that learning outcomes increase. The subjects of this research were students of the 6th semester of the Mathematics Education study program in the Elementary Linear Algebra course which consisted of 20 students. Meanwhile, the object of research is the improvement of students 'abilities in mathematical problems, increasing students' self-confidence and the ability of lecturers to learn through the Inquiry method. The conclusions that can be drawn from this study are 1) The ability of student learning outcomes in mathematics learning through the inquiry method in Elementary Linear Algebra is shown by the proportion of learning test results, namely 78.50% with the category "Enough" in the first cycle increased to 86.84% category "Good" in cycle II. 2) The ability of students' self-confidence using the observation method has increased when viewed from the student results in the first cycle with the proportion of 84.45% in the "Good" category, the proportion of observations of students in the second cycle becomes 94.57% in the "Very Good" category.